Analisis Kandungan Formalin dan Boraks Pada Bakso dan Tahu di Wilayah Kota Malang - Lukky Jayadi; Dwipajati Dwipajati; Nurma Sabila (Journal Syifa Sciences and Clinical Research, 2023)
The main danger posed by formalin and boric acid or often called borcas if exposed continuously is that it can irritate the respiratory tract if inhaled, cause skin blisters if in contact with skin, nausea, vomiting, diarrhea, possible bleeding, abdominal pain, headache, hypotension, fainting. to coma. In addition, formalin can cause degenerative changes in the liver, heart, brain, other organs and can trigger genetic mutations resulting in cell damage or cell death which can result in the growth of cancer cells. This study aims to identify the content of formalin and boric acid or borkas in food samples of meatballs and tofu. The method used in this research is to test for boric acid or borcass by using AgNO3 and Paper Test Kit and for testing Formalin using KMnO4 and Reagent Test Kit. This method is used as a qualitative test for the presence of formalin and borax or boric acid in the sample. A positive result for the presence of borax or boric acid with AgNO3 with the occurrence of a white precipitate and using a paper test kit will turn brown. To identify formalin, a positive result with KMnO4 is indicated by a change in color to brown and using a test kit reagent is indicated by a change in the color of the positive sample to purple. The samples tested were 3 meatball samples and 3 tofu samples. The results of the identification of formalin and borax or boric acid in all meatball and tofu samples were obtained using qualitative tests, no meatball and tofu samples containing formalin and borax or boric acid were found.